Diversity of Important Pests and Natural Enemies in Rice Plants - Nauval Zakqy; Sri Wiyatiningsih (Future Science, 2022)
The main obstacle that is often faced by farmers is the presence of Plant Pest Organisms (OPT), one of the pests is the types of pests on rice plants. Diversity of pests and natural enemies of rice is an activity of collecting and compiling data and information regarding the presence of pests and natural enemies in rice cultivation. The purpose of the study was to obtain data on the types of pests and natural enemies in lowland rice cultivation. The results showed important pests on rice plants, namely green leafhoppers (Nephotettix virescen), walang sangit (Leptocorisa oratorius), brown leafhoppers (Nilaparvata lugens), armyworms (Mythimna separate), grasshoppers (Oxysa spp), ganjur (Orseolia oryzea), birds finches (Lonchura sp) and mouse (Rattus argentiventer). As for natural enemies, namely spiders (Lycosidae), tomcat (Paederinae), dragonflies (Orthetrum Sabina), wasps (Vespula germanica) and beetle koksi (Coccinella septempunctata). The presence of natural enemies in rice cultivation can affect the level of pest populations in rice cultivation.